Empowerment of Togong-Tanga indigenous people through the development of apiculture-based conservation villages - Khasanah, Sofiana Nur; Setiadi, Achmad (Indonesian Journal of Multidisciplinary Science, 2024)
The Kokolomboi Lestari Program is a community empowerment initiative aimed at empowering the Togong-Tanga Indigenous Peoples in Central Sulawesi Province. It focuses on developing sustainable apiculture systems in Leme-Leme Darat Village, aiming to increase forest resource productivity and improve ecosystems and habitats for endemic animals. The program provides employment opportunities and income from forest bee management and environmental services. A study found that solid waste treatment from PT Pertamina EP Donggi Matindok Field operations contributes to global warming potential (GWP), with CO2, N2O, and CH4 emissions being major contributors. The program also uses non-B3 waste from fire truck tires as a conservation medium, and biosulfur slury as fertilizer for agricultural activities. This program has achieved sustainability goals, improving social life, economic and environmental standards, and strengthening the economy of indigenous peoples.